Analysis of numeracy skills in Islamic Boarding Schools: Gender bias - Bahar, Rosid; Firdaus, Ahmad (Psychology, Evaluation, and Technology in Educational Research, 2024)
Numeracy skills are an important point in the structure of mathematics, and boarding school students are no exception. This study aims to identify gender bias in numeracy assessment in Islamic boarding schools. This research is a descriptive exploratory research using quantitative methods. The instrument used in this study was a numeracy test of 25 questions consisting of matching, multiple-choice, complex multiple-choice, and description questions. The research subjects involved 383 students in West Java consisting of 4 pesantren in 4 cities, namely West Bandung Regency, Cirebon Regency, Tasikmalaya Regency, and Tasikmalaya City. Quantitative analysis used Item Response Theory (IRT) followed by Differential Item Functioning (DIF) analysis with the Mantel-Haenzel method. The results showed that the instrument was suitable for use because it met the standards of validity and reliability. The model fit test that meets is GPCM, and DIF analysis shows that there is 1 number, namely number 21, in numeracy questions that indicate gender bias. The results of this analysis indicate that the numeracy test instrument set is suitable for use by boarding school students with minimal gender bias.